2021
DOI: 10.1057/s41599-021-00750-9
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap! On the future of AI research

Abstract: Research on AI tends to analytically separate technical and social issues, viewing AI first as a technical object that only later, after it has been implemented, may have social consequences. This commentary paper discusses how some of the challenges of AI research relate to the gap between technological and social analyses, and it proposes steps ahead for how to practically achieve prosperous collaborations for future AI research. The discussion draws upon three examples to illustrate the analytical gap in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Earlier research has identified the need of multidisciplinary collaborations to assess the role and importance (impacts) of AI in society (e.g. Boyd and Wilson 2017 ; Theodorou and Dignum 2020 ; Dahlin 2021 ; De Neufville and Baum 2021 ). The basic argument follows the line of thought that AI concerns mainly technological development driven by engineering domains of science, whereas social sciences are focusing on social impacts and uneven developments caused by technological progression.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Earlier research has identified the need of multidisciplinary collaborations to assess the role and importance (impacts) of AI in society (e.g. Boyd and Wilson 2017 ; Theodorou and Dignum 2020 ; Dahlin 2021 ; De Neufville and Baum 2021 ). The basic argument follows the line of thought that AI concerns mainly technological development driven by engineering domains of science, whereas social sciences are focusing on social impacts and uneven developments caused by technological progression.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…To persuade healthcare systems to adopt machine learning in the future, implementation research needs to focus on demonstrating value-based care to garner funding. This funding will be especially critical for assessing algorithms in clinical trials that study not only ethnically diverse cohorts [71] but also clinical consequences as a result of implementation that may require recalibration of algorithms [72].…”
Section: Discussionmentioning
confidence: 99%
“…SAI enables companies to better understand the interaction of the three sustainability dimensions through time, thus considering short, long-term, and longer-term interactions 2015 The guiding principle of the 2030 Agenda pursues the goal of enabling a decent life worldwide while permanently preserving the natural foundations of life. Apart from van Wynsberghe (2021), recent works referring to the concept of SAI fail to provide a holistic definition (e.g., Yun et al 2016;Dhar 2020;Bjørlo et al 2021;Dahlin 2021;Fernandez-Aller et al 2021). For example, the working definition given by Bjørlo et al (2021) within the contextual boundaries of online decision-making is based on the Brundtland Report (World Commission on Environment and Development 1987).…”
Section: Sustainable Artificial Intelligence (Sai)mentioning
confidence: 99%